M2 Macrophages Serve as Critical Executor of Innate Immunity in Chronic Allograft Rejection - Zhang, Hanwen; Li, Zhuonan; Li, Wei (Frontiers in Immunology, 2021)
Allograft functional failure due to acute or chronic rejection has long been a major concern in the area of solid organ transplantation for decades. As critical component of innate immune system, the macrophages are unlikely to be exclusive for driving acute or chronic sterile inflammation against allografts. Traditionally, macrophages are classified into two types, M1 and M2 like macrophages, based on their functions. M1 macrophage is involved in acute rejection for triggering sterile inflammation thus lead to tissue damage and poor allograft survival, while M2 macrophages represent contradictory features that play pivotal roles in both anti-inflammation and development of graft fibrosis, resulting in chronic rejection. Macrophages also contribute to allograft vasculopathy, but the phenotypes remain to be identified. Moreover, increasing evidences are challenging traditional identification and classification of macrophage in various diseases. Better understanding the role of macrophage in chronic rejection is fundamental to developing innovative strategies for preventing late graft loss. In this review, we will update the recent progresse in our understanding of diversity of macrophage-dominated innate immune response, and reveal the roles of M2 macrophages in chronic allograft rejection as well.